Analisis Preferensi Petani Kelapa Sawit dalam Membeli Bibit Kelapa Sawit Bersertifikat di Kabupaten Batu Bara - Myrna Pratiwi Nasution; Putri Sina Br Tarigan (Fakultas Pertanian, Universitas Timor, 2021)
There are several factors that cause farmers to be less aware of the importance of the quality and productivity of oil palm plants, including lack of information and publications, lack of socialization on the use of quality seeds and limited farmer capital. From the producer side, in Indonesia there are several companies that produce certified oil palm seeds at various prices. This company offers seed prices starting from sprouts, 3 month old seeds and seeds more than 9 months old. The large number of certified seedlings offered has made the position of competition between brands to be tighter, which has prompted producers to continue to make good business strategies so that their products in the market can be accepted by consumers, especially palm oil entrepreneurs. The purpose of this study was to analyze the combination of certified seed products, product combination attributes, and farmers' preferences for the use of certified oil palm seeds. The data obtained during the study were processed using conjoint analysis. Research data were taken from 100 farmer respondents. The results of the research on the preferences of certified seed farmers that are very popular are certified seeds with attributes of type Dumpy from PPKS, 3 months old seeds, price range around Rp. 15.000, getting promotion from seed producers by 25%, very easy access to certified seeds, and it can be planted on surging land types. Farmer's Preference in buying oil palm seeds choose seed price as the most preferred attribute when purchasing certified seeds in Batu Bara District.